Influence of the Applied Potential and Temperature on the Electrode position of the Lead Dioxide - Khalaf, Taha Yaseen (Al-Khwarizmi Engineering Journal, 2013)
The excellent specifications of electrodes coated with lead dioxide material make it of great importance in the industry. So it was suggested this study, which includes electrodeposition of lead dioxide on graphite substrate, knowing that the electrodeposition of lead dioxide on graphite studied earlier in different ways. In this work the deposition process for lead dioxide conducted using electrolytic solution containing lead nitrate concentration 0.72 M with the addition of some other material to the solution, such as copper nitrate, nickel nitrate, sodium fluoride and cetyl trimethyl ammonium bromide, but only in very small concentrations. As for the operating conditions, the effect of change potential and temperature as well as the time on the deposition process was studied. The results shown at the end of the experiments that the change in the applied potential to the cell and electrolytic solution temperature had the greatest influence on the cell current, anodic current density, anodic overpotential and the amount of lead dioxide deposited on the anode.